Atlas de la memoria: museo judío de Berlín, centro de la memoria en Alemania (2019)
In the present article a reflection is proposed based on the work advanced in the seedbed of research Atlas of memory, the research project entitled "Design of urban and architectural memory in the Colombian post-conflict scenarios of peace", attached to the Faculty of Architecture of the Santo Tomas University of Tunja. This hotbed of research, propases to study different places that have been designed to honor the memory in conflict and post-conflict phases in the world, which serve as references in creation, architecture and design arts, far the reality that the Colombian nation lives in. Peace process that is being carried out with the Guerrilla of the FARC-EP and that has had an impact on the reality of the country, presenting the possibility of creating new scenarios far reconciliation far the fabric that has been affected by the war after 60 years of armed conflict. Far this purpose, in this document, first of all, a general presentation of the Jewish Museum of Berlín, in Germany, is made, explaining its motivations, processes and architecture; Secondly, the experience lived in the field work carried out in the place after the visit that was carried out was presented and resulted in a reflection on its historical peculiarities and values; and finally a discussion is proposed about their contributions to the construction of peace scenarios.